Brain metabolic correlates of decision making in amnestic mild cognitive impairment - Griffith, H. Randall (2010)
Persons with amnestic mild cognitive impairment (MCI) have subtle impairments in medical decision-making capacity (MDC). We examined the relationship between proton magnetic resonance spectroscopy (MRS) and MDC in MCI. Twenty-nine MCI patients and 42 controls underwent MRS to obtain ratios of N-acetylaspartate (NAA)/Creatine (Cr), Choline (Cho)/Cr, and myo-Inositol (mI)/Cr of the posterior cingulate. They also completed the Capacity to Consent to Treatment Instrument (CCTI), a vignette-based instrument measuring decisional standards of expressing choice, appreciating consequences of choice, providing rational reasons for choice, and understanding treatment choices. Patients showed abnormal MRS ratios of mI/Cr and Cho/Cr compared to controls, and impairments on the CCTI understanding and reasoning Standards. Performance on the Reasoning Standard of the CCTI was correlated with NAA/Cr (r = 0.46, p < 0.05). The relationship of NAA/Cr with decision-making suggests a role for posterior cortical neuronal functioning in performance of complex IADLs in MCI.